Let's solve each quadratic equation one by one:
-
Equation: \((x+3)(x−1)=0\)
To solve for \(x\):
- Set each factor to zero:
- \(x + 3 = 0\) ⟹ \(x = -3\)
- \(x - 1 = 0\) ⟹ \(x = 1\)
Answer: \(x = -3\) and \(x = 1\)
- Set each factor to zero:
-
Equation: \((15x−5)(7+x)=0\)
To solve for \(x\):
- Set each factor to zero:
- \(15x - 5 = 0\) ⟹ \(15x = 5\) ⟹ \(x = \frac{5}{15} = \frac{1}{3}\)
- \(7 + x = 0\) ⟹ \(x = -7\)
Answer: \(x = -7\) and \(x = \frac{1}{3}\)
- Set each factor to zero:
-
Equation: \((13x−2)(x−34)=0\)
To solve for \(x\):
- Set each factor to zero:
- \(13x - 2 = 0\) ⟹ \(13x = 2\) ⟹ \(x = \frac{2}{13}\)
- \(x - 34 = 0\) ⟹ \(x = 34\)
Answer: \(x = \frac{2}{13}\) and \(x = 34\)
- Set each factor to zero:
-
Equation: \(30 = x^2 + 13x\)
Rearrange this to standard form: \[ x^2 + 13x - 30 = 0 \]
Now, we can solve using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] where \(a = 1\), \(b = 13\), and \(c = -30\).
Calculate the discriminant: \[ b^2 - 4ac = 13^2 - 4(1)(-30) = 169 + 120 = 289 \]
Now, plug this into the quadratic formula: \[ x = \frac{-13 \pm \sqrt{289}}{2(1)} = \frac{-13 \pm 17}{2} \] Which gives:
- \(x = \frac{4}{2} = 2\)
- \(x = \frac{-30}{2} = -15\)
Answer: \(x = -15\) and \(x = 2\)
Here are the final answers summarized:
- Your Answer: \(x = -3\) and \(x = 1\)
- Your Answer: \(x = -7\) and \(x = \frac{1}{3}\)
- Your Answer: \(x = \frac{2}{13}\) and \(x = 34\)
- Your Answer: \(x = -15\) and \(x = 2\)